Investment behavior in a constrained dictator game - Michael Coenen; Dragan Jovanovic (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
We analyze a constrained dictator game in which the dictator splits a pie which will be subsequently created through simultaneous investments by herself and the recipient. We consider two treatments by varying the maximum attainable size of the pie leading to either high or low investment incentives. We find that constrained dictators and recipients invest less than a model with self-interested players would predict. While the splitting decisions of constrained dictators correspond to the theoretical predictions when investment incentives are high, they are more selfish when investment incentives are low. Overall, team productivity is negatively affected by lower investment incentives.
Keywords: C72; C91; D01; 330; Bargaining Game; Dictator Game; Investment Incentives; Team Production